Hubungan Daya Ledak Otot Tungkai dan Kekuatan Otot Perut Dengan Kemampuan Long Pass Pada Permainan Sepakbola Di SSB Putra Seki - Adam, Syahril; Iskandar, Egar (JIPOR: Jurnal IPTEK Olahraga dan Rekreasi, 2024)
This study aims to investigate the relationship between leg muscle explosive power and abdominal muscle strength with long pass ability in football at SSB Putra Seki. The research method used is a correlational method with a subject sampling technique of 30 male players aged 12-15 years. The instruments used were the vertical jump test to measure leg muscle explosive power, the sit-up test to measure abdominal muscle strength, and the long pass test to measure long-distance kicking ability. Data analysis used the product moment correlation. The results showed a significant relationship between leg muscle explosive power (r=0.770, p<0.05) and abdominal muscle strength (r=0.718, p<0.05) with long pass ability. In conclusion, there is a significant relationship between leg muscle explosive power and abdominal muscle strength collectively with long pass ability in SSB Putra Seki players. It is recommended that coaches provide training to improve leg muscle explosive power and abdominal muscle strength to optimize players' long pass ability.